American poetry 1946 to 1965 - Bloom, Harold (Critical cosmos series., 1987)
Critical essays on the works of some twenty-five poets, written after World War II. Includes poetry of Louise Bogan, Stanley Kunitz, Elizabeth Bishop, Robert Hayden, Sylvia Plath, and others.